A flor que nasce do impossível chão: lutas e resistência de mulheres negras na periferia da zona sul de São Paulo - Silva, Eliana Pereira (2020)
Postgraduate Studies Program in Social Work. Pontifical Catholic University of São Paulo, 2020. In the eyes of barbarism, black women correspond to that segment ofthe working class that is most at risk ofnot reproducing the minimum conditions oftheir livelihoods. Historically, these women are responsible for their own survival and that oftheir families, thus constituting expressive fractions of families subjected to overexploitation. In this context, racism and patriarchy are updated, promoting harmful consequences for the life of the population that makes up the base ofthe social pyramid. In times when the neoliberal offensive seeks to displace any perspective of collective organization, the forms of organization pointed out in this research reveal that, despite so many adversities, black and poor women are building alternatives to fight, resist and confront the historical inequalities that affect their everyday lives. Thus, the general goal of this research is to understand the struggles and resistance of black women in the periferias ofthe south zone of São Paulo-SP. As specific goal, we seek to identify and understand how collectives of struggles and resistance of poor and black women in the region are organized, by analyzing the impact of the repercussions of barbarism on the life trajectory of women and apprehending the ways in which gender class and race/ethnicity determinations affect the daily lives of these women. The investigation process involved both theoretical and field researeh which was carried out based on participant observation ofthe activities of feminist collectives working on the periferias of the southem part of São Paulo city, as well as individual interviews with militants, young people, active feminists in these collectives. The results ofthe research allow us to atY1tm that the historical process ofthe struggles and resistances promoted by the black population during slavery, added to the resistances built in the post-abolition process, forms, throughout the 20th century, an important legacy and reference for the current resistances. Mobilized by precarious living conditions and affected by the logic of urban spoliation, urban populations have organized themselves in the struggle for access to rights, improvements in living conditions and complaints about acts ofviolence in their territories. This type of resistance has as its main protagonist black women and young people Who still problematize the myth of racial democracy, bringing the legacy ofblack feminism and the denial of stereotypes historically attributed to black women. We highlight the naturalization of servile work as a destination, sexual objectification and denied motherhood. 'lhe problematization ofthese three aspects and the way they affect everyday life brings us closer to the reaffirmation ofthe struggle for human emancipation and the historical need for class organization, taking into account racism and sexism as onstituent axes ofthe processes of struggle